Informe pasantía de investigación: Prospectiva de las industrias culturales y creativas, sector editorial y audiovisual (2023)
This research report focuses on the cultural and creative industries (CCI) and its relevance in the development of different populations, specifically in the city of Bogotá. The behavior of the publishing and audiovisual sector in Colombia is examined and the necessary occupational profiles in this industry are analyzed. In addition, the implementation of the creative economy in government development plans is highlighted.